Immunogenicity and transmission-blocking potential of quiescin sulfhydryl oxidase in Plasmodium vivax - Zheng, Wenqi; Cheng, Shitong; Liu, Fei; Yu, Xinxin; Zhao, Yan; Yang, Fan; Thongpoon, Sataporn; Roobsoong, Wanlapa; Sattabongkot, Jetsumon; Luo, Enjie; Cui, Liwang; Cao, Yaming (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundTransmission-blocking vaccines (TBVs) can effectively prevent the community’s spread of malaria by targeting the antigens of mosquito sexual stage parasites. At present, only a few candidate antigens have demonstrated transmission-blocking activity (TBA) potential in P. vivax. Quiescin-sulfhydryl oxidase (QSOX) is a sexual stage protein in the rodent malaria parasite Plasmodium berghei and is associated with a critical role in protein folding by introducing disulfides into unfolded reduced proteins. Here, we reported the immunogenicity and transmission-blocking potency of the PvQSOX in P. vivax.Methods and findingsThe full-length recombinant PvQSOX protein (rPvQSOX) was expressed in the Escherichia coli expression system. The anti-rPvQSOX antibodies were generated following immunization with the rPvQSOX in rabbits. A parasite integration of the pvqsox gene into the P. berghei pbqsox gene knockout genome was developed to express full-length PvQSOX protein in P. berghei (Pv-Tr-PbQSOX). In western blot, the anti-rPvQSOX antibodies recognized the native PvQSOX protein expressed in transgenic P. berghei gametocyte and ookinete. In indirect immunofluorescence assays, the fluorescence signal was detected in the sexual stages, including gametocyte, gamete, zygote, and ookinete. Anti-rPvQSOX IgGs obviously inhibited the ookinetes and oocysts development both in vivo and in vitro using transgenic parasites. Direct membrane feeding assays of anti-rPvQSOX antibodies were conducted using four field P. vivax isolates (named isolates #1–4) in Thailand. Oocyst density in mosquitoes was significantly reduced by 32.00, 85.96, 43.52, and 66.03% with rabbit anti-rPvQSOX antibodies, respectively. The anti-rPvQSOX antibodies also showed a modest reduction of infection prevalence by 15, 15, 20, and 22.22%, respectively, as compared to the control, while the effect was insignificant. The variation in the DMFA results may be unrelated to the genetic polymorphisms. Compared to the P.vivax Salvador (Sal) I strain sequences, the pvqsox in isolate #1 showed no amino acid substitution, whereas isolates #2, #3, and #4 all had the M361I substitution.ConclusionsOur results suggest that PvQSOX could serve as a potential P. vivax TBVs candidate, which warrants further evaluation and optimization.